A Scor-based Model For Green Sales And Distribution Performance Measurement In The Leather Tanning Industry - Afifa Sucihana Ismadhia; Ari Yanuar Ridwan; Rosad Ma’ali El Hadi (JRSI (Jurnal Rekayasa Sistem dan Industri), 2018)
A green supply chain performance measurement system is needed to manage the environmental risks that are often being the major issues of industry. Claim from the government to implement the green supply chain system will certainly be a boost to major industries in Indonesia. As for PT. Elco lndonesia Sejahtera, to create an industry that applies green perspective in the industry, of course PT. EIS requires a model of its own enterprise performance measurement system design. Therefore, this study aims to design a performance measurement system from Green Sales and Distribution in the supply chain of leather tanning industry. The model used as a tool for designing performance measurement systems from the supply chain is Green SCOR model. The conceptual model is designed by involving activities such as stakeholder identification, needs analysis of green stakeholders, green destination identification, and KPI weighting. The supply chain operation reference metric (SCOR) is applied to identify key performance indicators (KPIs). The weight of the KPI is determined using the AHP method. The results of this study are six green objectives and also fifteen Key Performance indicators under it. Green objectives and Key performance can help companies to improve the performance of Green Sales and Distribution in the company.